(3GdJGL hGdEcdjd Ydi eNJUQ Ndjds - (3eMeO Hf jhSa Hf CHi Gd bGSe Hf jhSa GdYHOQi GdZQfGWi , CHh YHO Gddgs; (3Ndjd Hf ESMGb Hf ehSi, VjGA GdOjf GdoLrfpOj GdeGdcj GdeUQj,J (B776 (3g` s
(3ChdgG (B:s
(3JfbU ef ChdgG , hChd GedhhLhO (B: (3bhdg (B: (3hLGR ddeQCI GdedHhS eWdbkG GHf YQaI Mdi edHhS GdfSGA hdhPgHkG eHGM hai GHf jhfS eG jJNPg G dfGS dTYhQgf hCRQGQ LjhHge hGbaGd KjGHge heG jLQi LQi dHGSge adGRcGI ajg s
(3BNQgG (B:s
(3JfbU ef BNQgG , hBNQ GdehLhO (B: (3bhdg (B: (3hjLhR ef dfHgG eGdGjV HjJGegG , JbOe fU GHf TGS HgPG , hai VMGjGgG , bO Qhi ai GdMOjK (B: (3dGHCS HGdTQH efgG s
(3GdfSNI HgG MhGTs
(3fSNI edabI HNWjf eNJdajfs
(3eUMMI s
(3eWGdYI HgG fXGe GdJYbjHI s
(3HYV cdeGJgG HGdMeQI s
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdeGdcjs